Strategi Komunikasi Badan Nasional Penanggulangan Bencana dalam Program Desa Tangguh Bencana - Yuliani, Hafri; Ayuh, Eceh Trisna; Karina, Mely Eka (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This research aims to determine the communication strategy of the national disaster management agency in the Bengkulu City disaster resilient village village program. The method used in this research is a qualitative method with data collection techniques, namely observation, interviews and documentation. The research results show an increase in public awareness and knowledge, becoming more aware of the various types of disaster risks that may occur. Knowledge about disasters: The community gets more in-depth information about the causes, impacts and types of natural disasters such as earthquakes and tsunamis. Community emergency response skills are trained on safe and effective evacuation methods when a disaster occurs. First aid, training on how to provide first aid to disaster victims. Development of emergency response plans, with family plans and community plans. The use of technological equipment is trained by using fire extinguishers, flashlights, radio communications. Formation and strengthening of disaster volunteers. Increasing community resilience and preparedness, training is accompanied by simulations and disaster response exercises that help the community practice what they have learned. In conclusion, one of the efforts made by BNPB is to implement the IDRIP-DESTANA project, Diffusion (diffusio) Project by increasing community preparedness by providing education and training to the community regarding disasters, meeting 29 times. Keywords: Communication Strategy, Diffusion of Innovation, BNPB, DESTANA